Comparison Analysis of Road Performance Method Between MKJI 1997 and PKJI 2023 using Case Study at Jalan Jendral Ahmad Yani - Azimah, Nur Huwaida; Azwansyah, Heri; Kadarini, S. Nurlaily (Jurnal Teknik Sipil, 2024)
Road is critical part in transportation system. The existence of road can provide convenient and safe passage for various types of vehicles, including cars, buses, motorcycles and bicycles. The use of road can give impact like performance degradation over time, so there has to be some examinations for road performance. Based on aforementioned fact, this research will conduct road performance analysis using MKJI 1997 and PKJI 2023 method. The degree of saturation and road capacity are the comparison parameter for assessment. The objective of this research will compare the results from both method. Jalan Jendral Ahmad Yani will be the research object. On this road, all requirement data was collected to accommodate the analysis. The data collected was employed to calculate road performance for existing condition. From data of existing condition, Both method was implemented for 5-year projection. The projection was conducted to predict road performance considering the increase of population. The results from both method showed that the existing condition and 5-year projection were not qualified, because the level of service was very low. PKJI 2023 method resulted the higher number than MKJI 1997. This is because the parameter value from both method was stated differently. Considering bad performance of the road, the improvement step was taken to increase all parameters involved in the road performance. The improvement, Like enhancement on road geometric, effectively worked to increase the road performance.